2002
DOI: 10.1002/ijc.10234
|View full text |Cite
|
Sign up to set email alerts
|

Reduced poly(ADP‐ribosyl)ation in lymphocytes of laryngeal cancer patients: Results of a case‐control study

Abstract: Poly(ADP-ribose) polymerase (PARP), a nuclear enzyme that is catalytically activated by DNA strand breaks, plays a complex role in DNA repair. Using NAD ؉ as a precursor, it catalyzes the formation of ADP-ribose polymers, which are attached to various proteins. Defects in DNA repair pathways have been associated with increased risks for cancer in humans. We investigated whether differences in the activity of PARP are associated with the risk for laryngeal cancer. In a case-control study on genetic, lifestyle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 36 publications
1
18
0
1
Order By: Relevance
“…In addition, recent epidemiological studies showed that a single nucleotide polymorphism of PARP-1 (Val762Ala) was associated with human prostate, esophageal and lung carcinomas (Hao et al, 2004;Lockett et al, 2004;Zhang et al, 2005). Moreover, downregulation of the PARP-1 activity has been observed in peripheral mononuclear leukocytes of breast (Hu et al, 1997), head and neck (Rajaee-Behbahani et al, 2002) and prostate cancer patients (Lockett et al, 2004), suggesting that genetic variants and alteration of PARP-1 enzymatic activity may contribute to human carcinogenesis (Shiokawa et al, 2005). In this report, we have provided compelling in vivo evidence that PARP-1 deficiency causes mouse mammary carcinomas.…”
Section: Discussionmentioning
confidence: 64%
“…In addition, recent epidemiological studies showed that a single nucleotide polymorphism of PARP-1 (Val762Ala) was associated with human prostate, esophageal and lung carcinomas (Hao et al, 2004;Lockett et al, 2004;Zhang et al, 2005). Moreover, downregulation of the PARP-1 activity has been observed in peripheral mononuclear leukocytes of breast (Hu et al, 1997), head and neck (Rajaee-Behbahani et al, 2002) and prostate cancer patients (Lockett et al, 2004), suggesting that genetic variants and alteration of PARP-1 enzymatic activity may contribute to human carcinogenesis (Shiokawa et al, 2005). In this report, we have provided compelling in vivo evidence that PARP-1 deficiency causes mouse mammary carcinomas.…”
Section: Discussionmentioning
confidence: 64%
“…The results from these studies suggest that base excision repair (BER) is involved in CaP susceptibility (3,4,6,7). Because adenosine diphosphate ribosyl transferase/ poly(ADP-ribose) polymerase-1 (ADPRT/PARP-1) plays a critical role in both BER and maintaining the genomic stability of cells exposed to genotoxic stress and because previous studies associated higher ADPRT/PARP-1 enzyme activation with lower human cancer risk (8,9), we hypothesize that genetic polymorphisms of ADPRT may contribute to lower enzyme activity and CaP risk.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of PARP-1 by genotoxic stimuli facilitates cell survival. The lymphocytes of cancer patients show a lower expression of PARP-1, which may indicate a higher level of DNA damaged (Rajaee-Behbahani et al 2002). This molecule has been found a potential target for the development of pharmacological strategies to increase the antitumor efficacy of chemotherapeutic agents that induce DNA damage in cancer cells (Peralta-Leal et al 2008).…”
Section: Discussionmentioning
confidence: 99%